System level design from HW/SW to memory for embedded systems : 5th IFIP TC 10 International Embedded Systems Symposium, IESS 2015, Foz do Iguaçu, Brazil, November 3-6, 2015, Proceedings /: 5th IFIP TC 10 International Embedded Systems Symposium, IESS 2015, Foz do Iguaçu, Brazil, November 3-6, 2015, Proceedings. (2017) - Unknown
No abstract available